Free riding on short-time work allowances? Results from an experimental survey design - Mario Bossler; Christopher Osiander; Julia Schmidtke; Mark Trappmann (Kyklos, 2023)
Short-time work (STW) is a policy measure whose prominence increases during economic crises and is intended to stabilize the labor market. Employers can temporarily reduce employees' working hours, which are in turn paid by the social security system in the meantime. Although short-time work—by design—saves employers a fraction of their wage costs, little is known about free riding behavior when using this option. Accordingly, we analyze the employee-reported free riding experience with respect to longer actual working hours than accounted for in employees' short-time work allowances, the unchanged workloads experienced by these employees, and announced lay-off decisions. Since these questions are certainly sensitive, we employ the crosswise model, a privacy-preserving technique, in a random half of the sample. Our results show significant employee-reported prevalences across all dimensions and a significant association between free riding and workers' job dissatisfaction. These findings thus highlight the importance of the crosswise model in uncovering these findings and demonstrate a specific drawback in the application of short-time work.
Keywords: 300